2019
DOI: 10.1111/fwb.13290
|View full text |Cite
|
Sign up to set email alerts
|

Macrophyte‐specific effects on epiphyton quality and quantity and resulting effects on grazing macroinvertebrates

Abstract: Aquatic macrophytes can have a significant impact on their associated community of epiphytic algae and bacteria through the provisioning of structural habitat complexity through different growth forms, the exudation of nutrients and the release of allelochemicals. In turn, this effect on epiphytic biofilm biomass and nutrient content has a potential effect on the macroinvertebrates that depend on epiphyton as a food source. We studied the effect of living macrophytes and their growth form on biofilm developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Both biofilm communities showed a dominant heterotrophy similar to previous studies, e.g., [57,58]. However, we also found that epiphyton showed higher heterotrophy compared to epilithon, which suggests macrophytes to be a more favourable substrate for the heterotrophic community compared to the gravel/stone substrate [59].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Both biofilm communities showed a dominant heterotrophy similar to previous studies, e.g., [57,58]. However, we also found that epiphyton showed higher heterotrophy compared to epilithon, which suggests macrophytes to be a more favourable substrate for the heterotrophic community compared to the gravel/stone substrate [59].…”
Section: Discussionsupporting
confidence: 88%
“…The influence of hydrology (i.e., discharge, current velocity, low flow, high flow) on the epilithon structure was highly recognized in many previous studies in lotic systems [6,[67][68][69] and nutrients were identified as an important factor in driving epilithic diatom composition [28,55]. Furthermore, the low association of epiphyton with water nutrient concentrations supports the suggestion that the epiphyton community may depend on nutrients released from the macrophyte [13,59]. Our results support results from Gosselain et al [70] highlighting that epiphyton was related to physical variables such as light, macrophyte architecture and hydrology (i.e., seasonal water level variations) in the order of decreasing importance.…”
Section: Discussionmentioning
confidence: 66%
“…Macrophyte species with a complex morphology have a larger effect on flow velocity reduction and nutrient uptake than macrophytes with a simple morphology (e.g., with strap‐like leaves) (Levi et al, 2015; Sand‐Jensen & Mebus, 1996; Sand‐Jensen & Pedersen, 1999). Moreover, when macrophytes have a large leaf area they can take up more nutrients, provide a larger substrate to epiphytes that take up nutrients (Wolters et al, 2019) and sediment retention increases (Clarke, 2002). Between species, there can be large differences in leaf surface area and morphology (Levi et al, 2015), but differences can also exist within species, showing that there are interactions between macrophyte morphology and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mats of Phormidium were abundant in the afforested streams near the beginning of the experiment, which may have contributed to less grazing because the filamentous morphology, densely layered colonies, and chemical compounds produced by Phormidium make it less palatable for invertebrate grazers. Compared to biofilm on artificial plants, more nutritious biofilm with lower C:N:P developed on living macrophytes, which could be explained by nutrient exudates from the plants (Wolters et al, 2019). However, differences in nutritional content did not lead to increased grazer growth, perhaps because ANNUAL LITERATURE REVIEW grazers fed less nutritious biofilm compensated by consuming greater quantities of biofilm.…”
Section: Algal Ecologymentioning
confidence: 99%